Managing older people with diabetes in care homes. Issue 1 (2nd January 2017) - Dunning, Trisha; Sinclair, Alan J.
Abstract : This paper discusses some of key issues that need to be considered when caring for older people with diabetes living in care homes. It refers to but does not reproduce diabetes management information available in diabetes clinical guidelines such as Sinclair et al . [Diabetes mellitus in older people position statement on behalf of the International Association of Gerontology and Geriatrics (IAGG) and the European Diabetes Working Party for Older People (EDWOP) and the International Task force Experts in Diabetes. J Am Med Dir Assoc. 2012;13:497–502], International Diabetes Federation (IDF) [Global guideline for managing older people with type 2 diabetes. 2013. Available fromwww.idf.org ] and Dunning et al . [2013. Available fromhttp://www.adma.org.au/clearinghouse/doc_details/133-the-mckellar-guidelines-for-managing-older-people-with-diabetes-in-residential-and-other-care-settings_9dec2013.html ] guidelines. It does address care issues such as sexual health and wellbeing and companion animals that are rarely, if ever, described in clinical guidelines, yet they are essential to the quality of life and psychological wellbeing of many older people with and those without diabetes.